2016
DOI: 10.5194/esd-7-295-2016
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Ocean as a constraint to reduce uncertainty in future ocean carbon sinks

Abstract: Abstract. Earth system model (ESM) simulations exhibit large biases compares to observation-based estimates of the present ocean CO 2 sink. The inter-model spread in projections increases nearly 2-fold by the end of the 21st century and therefore contributes significantly to the uncertainty of future climate projections. In this study, the Southern Ocean (SO) is shown to be one of the hot-spot regions for future uptake of anthropogenic CO 2 , characterized by both the solubility pump and biologically mediated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…Hence, the air-sea CO 2 flux simulation spread needs to be narrowed to reduce the uncertainty in future climate projections. Kessler and Tjiputra31 have proposed that the air-sea CO 2 fluxes in the Southern Ocean could be used to constrain the future global ocean carbon uptake uncertainty. In this paper, two other methods are used to narrow the projected spread of air-sea CO 2 fluxes.…”
mentioning
confidence: 99%
“…Hence, the air-sea CO 2 flux simulation spread needs to be narrowed to reduce the uncertainty in future climate projections. Kessler and Tjiputra31 have proposed that the air-sea CO 2 fluxes in the Southern Ocean could be used to constrain the future global ocean carbon uptake uncertainty. In this paper, two other methods are used to narrow the projected spread of air-sea CO 2 fluxes.…”
mentioning
confidence: 99%
“…Though this relationship between dSST and dpCO 2 is based on a linear assumption (Takahashi et al, 1993), this formulation has been shown to hold and has been widely used in the literature (e.g., Bakker et al, 2014;Feely et al, 2004;Marinov and Gnanadesikan, 2011;Takahashi et al, 2002;Wanninkhof et al, 2009;Landschützer et al, 2018). We show in the Supplement that the extension of this expression into polar temperature ranges (SST < 2 • C) only introduces a minor additional uncertainty of 4-5 % (SM Fig.…”
Section: ∂Dic ∂Tmentioning
confidence: 86%
“…The emergent constraint approach has been applied to link air-sea flux changes in the tropics (Wenzel et al, 2014) and the Southern Ocean (Kessler and Tjiputra, 2016) as simulated by different ESMs to observational signals (tropical temperatures) or potentially observable flux changes (Southern Ocean CO2 uptake strength). Kwiatkowski (2017) found an emergent constraint on narrowing down the uncertainties in declining primary production at low latitudes.…”
Section: A19 Evaluation Of Marine Biogeochemical Feedbacks (See Alsomentioning
confidence: 99%
“…2017)) focuses on diagnosing forcings and feedbacks from near-term climate forcers.In addition to the CMIP6 experimental design, progress in constraining individual feedbacks and in equilibrium climate sensitivity, TCR, and the transient climate response to cumulative carbon emissions (TCRE) can be expected from emergent constraint studies (e.g Cox et al (2013)Hall and Qu (2006);Kessler and Tjiputra (2016);Wenzel et al (2014); Wenzel et al…”
mentioning
confidence: 99%